Highly selective and robust PDMS mixed matrix membranes by embedding two-dimensional ZIF-L for alcohol permselective pervaporation - Mao, Heng; Zhen, Hong-Gang; Ahmad, Ali; Li, Shen-Hui; Liang, Yue; Ding, Jun-Fan; Wu, Yao; Li, Lin-Zhi; Zhao, Zhi-Ping (Journal of membrane science, 2019)
High separation performance and superior mechanical properties of the membranes are both of critical importance for membrane modules to achieve high efficiency and long-term stability. Herein, a series of mixed matrix membranes (MMMs) with brick-and-mortar architecture are prepared by incorporating two-dimensional zeolitic imidazolate framework-L (ZIF-L) nanosheets into polydimethylsiloxane (PDMS) matrix for separating alcohols (ethanol, n-propanol or n-butanol) from aqueous solution. The unique leaf-like morphology, flexible pore structure, and high hydrophobicity of ZIF-L nanosheets allow the straight and preferential permeation for alcohols; while the brick-and-mortar architecture renders the tortuous and intricate pathways for water, thus improving the membrane selectivity. Incorporating ZIF-L nanosheets endows the membranes with outstanding pervaporation performance, together with unusual and favorable increase in mechanical properties. More interestingly, the subtle interconnection of ZIF-L nanosheets creates the relatively continuous pathways for penetrants. Consequently, the resultant membrane displays a high separation factor (57.6) and a comparable permeation flux (402 g m−2 h−1) in separating 1.0 wt% n-butanol aqueous solution at 40 °C. Furthermore, the presence of ZIF-L nanosheets donates good thermal properties and promising long-term stability to the membranes. The findings of engineering brick-and-mortar architecture through two-dimensional porous fillers may provide new insights into designing high-performance MOF-based membranes for various applications. [Display omitted] •2D porous ZIF-L nanosheets were incorporated in PDMS matrix to prepare MMMs.•Interconnected nanosheets created relatively continuous pathways for penetrants.•Incorporating ZIF-L nanosheets enhanced selectivity and mechanical properties.•ZIF-L nanosheets notably reduced the permeation energy barriers for penetrants.•The MMMs exhibited superior pervaporation performance for alcohol recovery.